PENGEMBANGAN E-BAHAN AJAR BERBANTUAN AUGMENTED REALITY UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPAS SISWA SD - Tsabita Daffa Adilia; Tri Astuti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This research was conducted because the science learning process at SDN Ngadirgo 02 is still dominated by the use of conventional teaching materials, so that student motivation and learning outcomes are not optimal. The research aims to develop e-teaching materials assisted by Augmented Reality (AR) and test its feasibility and effectiveness in improving the motivation and learning outcomes of fourth-grade students on the topic